Cost-benefit analysis of agroecologically upgraded business models: A practitioner’s guide - Narjes, Manuel; Gonzalez, Carolina; Charry, Andrés (2024)
AE-I’s WP3 work adheres to following logic: after identifying the challenges and potential for integrating agroecological principles into a particular business model (e.g., by applying the Holistic Business Model Assessment suite), an upgrading plan or new business model is co-designed. The next step consists of co-developing an investment case, which among others requires demonstrating the profitability of the upgraded/new business model. Cost-Benefit Analysis (CBA) is at the core of investment appraisal and, in this guideline, will serve to assess the economic viability and competitiveness of upgrading business models through agroecological innovations.